Continuum of Care as An Effort to Reduce Stunting Events in Karawang District - Siti Sopiatun; Sri Maryati (Poltekkes Kemenkes Jakarta III, 2020)
Stunting is a condition of failure to thrive in children under five years due to chronic malnutrition so that the child is too short for his age. Malnutrition appears when the baby is in the womb and the early period after the baby is born. The purpose of this study is how the Continuum of Care Program is implemented, analyze cross-sectoral, and cross-program support in nutritional surveillance to prevent and manage stunting. The study design used a cross-sectional survey approach. The results of research from 6 Puskesmas working areas showed the highest number in Puskesmas Lemah Duhur with an incidence of stunting 81%, had a continuum of ineffective stunting treatments with an average of 63.84 and less available treatment centers with an average of 63.75. There are obstacles in sending information that occurs from the Puskesmas to posyandu cadres related to stunting. The range of treatments in providing effective care and place of care has the most significant impact on maternal health, the health of newborns, and children related to the incidence of stunting in each region. Collaboration and cross-sector programs are needed in stunting prevention by the government.